PERBANDINGAN HASIL BELAJAR KIMIA SISWA MENGGUNAKAN MODEL PEMBELAJARAN WORD SQUARE DAN MODEL PEMBELAJARAN SCRAMBLE DI MAN 2 KOTA BENGKULU - Weny Shintia; Amrul Bahar; Rina Elvia (University of Bengkulu, 2019)
This study aimed to compare the chemistry learning outcomes of students with using word square model learning and scramble model learning in grade X MAN 2 Kota Bengkulu on the subject of chemistry compound nomenclature. This was quasy experimental research and held in March to May 2018. Population in this study is the entire class X MIA in MAN 2 Kota Bengkulu 2017/2018 academic year, amounting to 149 students. Sample is class X MIA 1 and class X MIA 3. The sample of the research is class X MIA 1 with 32 students and class X MIA 3 with 33 students. Data analysis used normality test, homogeneity test and hypothesis test (t test). Data analysis was performed using Statistical Package for The Social Science (SPSS) version 16.Improvement student’s learning outcomes in this research was taken from difference assess of pretest and posttest. At experiment class of I average value improvement of student’s learning outcomes was 50.32. while at experiment class of II, average value improvement of student’s learning outcomes was 44.4 . through some statistic test, there was t-test (? = 0.05) which done test the hypothesis to obtained the test result was t value = 2.174 and t tabel = 1.998. The result of data analysis showed that were significant differences in student learning outcomes between the class which implemented word square model learning and the class which implemented scramble model learning. Student learning outcomes that apply the word square model of learning better than student learning outcomes that apply the scramble model of learning.